(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To identify strategies for the prevention of skin lesions in hospitalized newborns (NBs), published in scientific journals from 2013 to 2018. Method: Integrative literature review performed in two moments of database search, selecting 37 studies published between 2013 and 2018. Results: Thermoregulation, use of antiseptic, use of emollients and cleaning of the umbilical stump were the most commonly found recommendations. Among the evidence-based practices, we highlight those that prevent the risk of hypothermia, such as the use of a polyethylene bag and skin-to-skin contact, which support the assistance and ensure safety in the care of the neonatal patient. Conclusion: The prevention of skin lesions is a relevant topic. However, there is a scarcity of robust evidence to safely sustain NB care practices. It is also observed that the evidence is insufficient to encompass the universe of the theme, demonstrating that skincare is a theme that requires investment and more research.